2016
DOI: 10.1186/s12917-016-0889-z
|View full text |Cite
|
Sign up to set email alerts
|

Normal patellofemoral kinematic patterns during daily activities in dogs

Abstract: BackgroundPatellar abnormalities are a common cause of pain and lameness in dogs; however, in vivo the relative motion between the femur and patella in dogs is not well described. The objective of this study was to define normal in vivo sagittal plane patellofemoral kinematics in three axes of motion using non-invasive methods. We hypothesized patellofemoral alignment in the sagittal plane would tightly correlate with the femorotibial flexion angle. Six healthy dogs without orthopedic disease underwent compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…12,25 Conversely, in an in vivo evaluation of PF joint kinematics using single, sagittal plane fluoroscopy in dogs with cranial cruciate ligament deficient stifles, the entire patella was displaced distally throughout the gait cycle. 28,29 This distal displacement of the patella was attributed to the increased femorotibial flexion angle noted in dogs with cranial cruciate ligament deficient stifles at a walk and suggested that the proximal trochlear groove cartilage lesions may be induced by inadequate PF contact 28 rather than a proximal shift in contact area. 12,25 Despite the unknown reason for induction of cartilage damage at the proximal trochlear groove location, it is known that abnormal joint loading and alignment are risk factors for the development of osteoarthritis.…”
Section: Discussionmentioning
confidence: 98%
“…12,25 Conversely, in an in vivo evaluation of PF joint kinematics using single, sagittal plane fluoroscopy in dogs with cranial cruciate ligament deficient stifles, the entire patella was displaced distally throughout the gait cycle. 28,29 This distal displacement of the patella was attributed to the increased femorotibial flexion angle noted in dogs with cranial cruciate ligament deficient stifles at a walk and suggested that the proximal trochlear groove cartilage lesions may be induced by inadequate PF contact 28 rather than a proximal shift in contact area. 12,25 Despite the unknown reason for induction of cartilage damage at the proximal trochlear groove location, it is known that abnormal joint loading and alignment are risk factors for the development of osteoarthritis.…”
Section: Discussionmentioning
confidence: 98%
“…Three-dimensional digital bone models of the affected and contralateral femurs and patellas were created; the cortical bone margins were segmented using an open source 3D segmentation software program 3 , and these point-clouds were converted into polygonal surface models with a reverse engineering software program 4 . Anatomic coordinate systems were applied to the bone models based on anatomical landmarks of the patella and femur [ 23 ]. Femoral coordinates were applied such that the mediolateral axis (z-axis) passed through the center of the lateral and medial femoral condyles with the femoral origin located at the mid-point between the condyles (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The digital bone models of the patella and femur were superimposed over the fluoroscopic images and their projected silhouettes were translated and rotated such that the contours precisely matched the corresponding contours of the fluoroscopic images 5 , as previously described (Fig. 2 ) [ 23 ]. The patella was positioned centrally within the trochlear groove, such that the articulating surface of the patella at the center of the patella remained as congruent as possible with the trochlear groove in the axial plane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations